THE TEACHERS' USE OF ENGLISH TEXTBOOKS AT A MADRASAH ALIYAH IN CONJUNCTION WITH THE SCHOOL VISION AND MISSIONS :A Case study at a Madrasah Aliyah in Pangkalpinang-Bangka - Raharjo, Tri Edy Kesumo (2009)
This study reports on the teachers' use of English textbooks at a Madrasah Aliyah related to the school vision and missions. This study attempts to address the following questions; (1) How does teachers' understanding on the school vision and missions affect their teaching practices? (2) What is the teachers' opinion on the relevance of the textbooks on the school vision and missions? (3) How do the teachers select the textbooks and implement them in teaching practices? This study is conducted at a Madrasah Aliyah in Pangkalpinang. This study uses qualitative approach, particularly case study. The data for the study are obtained through three instruments; the questionnaire, interview, and observation. The questionnaire is distributed to obtain general views related to the three research questions. The interview is conducted to obtain the clarification of the data from the questionnaire. The observation is done during the interaction in the teaching learning process to observe the teachers' activities in selecting the textbooks use and implementing them in the teaching learning process. The subjects of this study are three English teachers at a Madrasah Aliyah in Pangkalpinang who teach the first, the second, and the third year classes. The findings reveal that, (1) the teachers' understanding on the school vision and missions do not affect their teaching. The teachers focus on the achievement of the national exam score rather than on the school vision and missions, (2) the textbooks the teachers use are not relevance with the school vision and missions. The textbooks that the teachers used contain general topics of discussions where there is no Islamic-oriented topic to be discussed, (3) the way the teachers select the textbooks is suited with the national curriculum and the way they implement teaching is the same as those of the general school teachers do, but they sometimes discuss the Islamic-oriented texts of some Islamic moments. Based on the finding it is recommended that the English teachers of Madrasah Aliyah use suitable textbooks with the school vision and missions. As well, this study is hoped to inspire other researchers to conduct the similar research of the textbooks use conducted by involving more participants and taking longer time.